A critique of Coleman - De Luccia - Perimeter Institute (Perimeter Institute, 2011)
In many respects, de Sitter space behaves like a system at finite temperature in finite volume. I will extend this to include the lack of first-order phase transitions. This rules out exponential decay in the de Sitter landscape, which changes the global structure in a significant way.
Keywords: Cosmology